2016
DOI: 10.1177/0271678x16647738
|View full text |Cite|
|
Sign up to set email alerts
|

Lithium-induced neuroprotection in stroke involves increased miR-124 expression, reduced RE1-silencing transcription factor abundance and decreased protein deubiquitination by GSK3β inhibition-independent pathways

Abstract: Lithium promotes acute poststroke neuronal survival, which includes mechanisms that are not limited to GSK3b inhibition. However, whether lithium induces long-term neuroprotection and enhanced brain remodeling is unclear. Therefore, mice were exposed to transient middle cerebral artery occlusion and lithium (1 mg/kg bolus followed by 2 mg/kg/day over up to 7 days) was intraperitoneally administered starting 0-9 h after reperfusion onset. Delivery of lithium no later than 6 h reduced infarct volume on day 2 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 56 publications
2
38
0
Order By: Relevance
“…Therefore, patients at risk for stroke with unfortunate collateral status (thus portending poor outcome) could particularly profit from a lithium treatment at low concentrations via a generally improved endothelium-dependent vessel relaxation capacity. This might be speculative, but on the other hand, the lithium-augmented cerebrovascular relaxation capacity may party explain, why continuous lithium treatment can reduce the risk for stroke (Lan et al, 2015) or may improve neurologic recovery after cortical stroke (Mohammadianinejad et al, 2014) potentially caused by various beneficiary effects on neurons (Doeppner et al, 2016; Vosahlikova and Svoboda, 2016), or platelets (Barry et al, 2003) including the direct ones on vascular and cerebrovascular endothelium (Afsharimani et al, 2007; Rahimzadeh-Rofouyi et al, 2007; Bosche et al, 2013, 2016), as presented here. Directly or secondarily impaired endothelial barrier after ischemia and hemorrhages followed by vasogenic edema formation (Stokum et al, 2016) were known to be highly relevant for clinical outcome of various types of stroke (Hacke et al, 1996; Bosche et al, 2003; Macdonald, 2014; Wijdicks et al, 2014; Urday et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, patients at risk for stroke with unfortunate collateral status (thus portending poor outcome) could particularly profit from a lithium treatment at low concentrations via a generally improved endothelium-dependent vessel relaxation capacity. This might be speculative, but on the other hand, the lithium-augmented cerebrovascular relaxation capacity may party explain, why continuous lithium treatment can reduce the risk for stroke (Lan et al, 2015) or may improve neurologic recovery after cortical stroke (Mohammadianinejad et al, 2014) potentially caused by various beneficiary effects on neurons (Doeppner et al, 2016; Vosahlikova and Svoboda, 2016), or platelets (Barry et al, 2003) including the direct ones on vascular and cerebrovascular endothelium (Afsharimani et al, 2007; Rahimzadeh-Rofouyi et al, 2007; Bosche et al, 2013, 2016), as presented here. Directly or secondarily impaired endothelial barrier after ischemia and hemorrhages followed by vasogenic edema formation (Stokum et al, 2016) were known to be highly relevant for clinical outcome of various types of stroke (Hacke et al, 1996; Bosche et al, 2003; Macdonald, 2014; Wijdicks et al, 2014; Urday et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Safe therapeutic concentrations of lithium are typically below 1 mol/L in these patients (Geddes and Miklowitz, 2013; Yatham et al, 2013; Mohammad and Osser, 2014). In preclinical and clinical research, lithium was recognized for robust neuroprotective effects regarding various pathologic conditions (Vo et al, 2015; Doeppner et al, 2016; Vosahlikova and Svoboda, 2016). Recent studies have also identified protective effects of lithium in cardiovascular and cerebrovascular diseases (Gold et al, 2011; Chiu and Chuang, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism of this effect, however, was not clear. Recently, a study showed that brain protection depends on nuclear REST degradation, upon which Li promotes post-ischemic neuroplasticity and angiogenesis [61]. The other study reported that known protection of synaptic damage by Li is due to its binding to nuclear REST in competition to a specific prion protein.…”
Section: Therapymentioning
confidence: 99%
“…Anti-axonal growth Inhibition of miR-124 activating PI3K/AKT/mTOR/GAP-43 pathway [39] Anti-apoptosis Activating PI3K/AKT/ Bcl-2 signaling pathway [40] Activating PI3K/AKT/Nrf2 signaling pathway [41] Anti-oxidative stress Activating PI3K/AKT/Nrf2 signaling pathway [41] Inhibitory member of the apoptosis-stimulating proteins of p53 family iASPP Pro-apoptosis Downregulating the expression of iASPP [36] B-cell lymphoma-2 B-cell lymphoma-extra large Bcl-2/Bcl-xl Anti-apoptosis Upregulating the expression of Bcl-2 and Bcl-xl respectively [42] Janus kinase 2 JAK2 Anti-apoptosis Activating JAK2/STAT3/Bcl-2 signaling pathway [16] X-ray repair cross-complementing protein 6 Ku70 Pro-apoptosis Knockdown of miR-124 attenuates I/R-induced apoptosis via negatively regulating Ku 70 [43] CCAAT/enhancer-binding protein alpha C/EBP-α Anti-inflammation Inhibiting C/EBP-α/PU.1 signaling pathway [22] RE1-silencing transcription factor REST Neuroplasticity Angiogenesis Facilitating REST degradation [44] Alzheimer's disease…”
Section: Neuronal Differentiation Neurovascular Remodelingmentioning
confidence: 99%